2012
DOI: 10.1111/j.1369-1600.2012.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain‐derived neurotrophic factor levels were reduced during methamphetamine early withdrawal

Abstract: Methamphetamine (METH) abuse is an increasing public health problem worldwide. Many of the METH-induced physical and mental problems are associated with the neurotoxic effects of METH. Animal studies have shown that brain-derived neurotrophic factor (BDNF) decreased after repeated amphetamine administration and increased at 30 and 90 days from psychostimulant withdrawal, suggesting that there might be a psychostimulant-induced neuroprotective dysfunction followed by a neuroadaptive process in the brain. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
(19 reference statements)
5
26
0
Order By: Relevance
“…Thus, we conclude that exposure to EE decreases the rewarding effects of METH which can reduce the risk of sensitivity and drug seeking after withdrawal [40]. The dopaminergic dysfunction [39], the low level of glutamate [2], and reduction of BDNF [6,14] may play a significant role in relapse of METH-seeking after protracted abstinence. In this regard, it has been shown that EE prevents methamphetamine-induced decrease of BDNF level after cessation of treatment with METH [6,14,15].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, we conclude that exposure to EE decreases the rewarding effects of METH which can reduce the risk of sensitivity and drug seeking after withdrawal [40]. The dopaminergic dysfunction [39], the low level of glutamate [2], and reduction of BDNF [6,14] may play a significant role in relapse of METH-seeking after protracted abstinence. In this regard, it has been shown that EE prevents methamphetamine-induced decrease of BDNF level after cessation of treatment with METH [6,14,15].…”
Section: Discussionmentioning
confidence: 82%
“…The dopaminergic dysfunction [39], the low level of glutamate [2], and reduction of BDNF [6,14] may play a significant role in relapse of METH-seeking after protracted abstinence. In this regard, it has been shown that EE prevents methamphetamine-induced decrease of BDNF level after cessation of treatment with METH [6,14,15]. Also, it seems that antidepressant and antianxiety effects of enriched environment decreased voluntary METH consumption in withdrawn rats.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that plasma BDNF levels are increased in drug addicts [46], and that serum levels decline with withdrawal [47]. However, other studies have shown that BDNF levels in the serum of methamphetamine addicts during withdrawal were lower than in controls [48]. Timing is a factor in these conflicting conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, one study reported the opposite result with decrease of serum BDNF during acute withdrawal in methamphetamine abusers. 12 It seemed that BDNF decreased first and then increased after methamphetamine withdrawal in humans. They explained that the neurotoxicity of methamphetamine could induce an impairment of neuroprotective function followed by a neuroadaptive process in the brain.…”
Section: Serum Bdnf Levels and Cognitive Function: Relationship To Vamentioning
confidence: 99%
“…11 In clinical research, the change of BDNF during methamphetamine withdrawal has been reported in 2 studies, but the results were inconsistent with each other. 7,12 Addictive drugs will also change the BDNF gene transcription, such as promoting BDNF exon IV expression in rat prefrontal cortex. 13 It has been reported that the BDNF gene might be an important factor in susceptibility to drug dependence or abuse.…”
mentioning
confidence: 99%